BUSINESS STRATEGY FORMULATION FOR HUMBLEZING TO OBTAIN SUSTAINABLE COMPETITIVE ADVANTAGE IN COMPETITIVE MARKET (The Indonesian Journal of Business Administration, 2019)
Building a sustainable competitive advantages is crucial to winning the competitive fashion industry. The purpose of this study was to design a business strategy to create the sustainable competitive advantage. Research initiated by analyse the external and internal factor of the company including PESTEL analysis, Porter’s five forces, competitor analysis, Porter’s value chain analysis, Resourced-based view and VRIO analysis. The methodological approach that used are integrating quantitative and qualitative data. Observation and questionnaire data will be collected to generate the SWOT matrix, TOWS matrix, Porter’s three generic strategies, Proposed business model canvas, and Proposed sustainable competitive advantages. The result showed that the best strategy for Humblezing can be tailored to sustain the business in competitive environment is focus differentiation. Where the company will emphasize the innovation in terms of product, variations, excellent customer service, digital marketing and brand communication. Then the sustainable competitive advantages will be obtained through powerful brand value, prospensity to innovation, customer co-creation and loyalty, and also the management system.Keywords : business model canvas, business strategy, fashion industry, humblezing, sustainable competitive advantage